The Many Faces of Nature: An Ecocritical Reading of the Concepts of Wilderness and the Sublime in John Keats’ Selected Poems - EMAMGHOLI TABAR MALAKSHAH, Morteza; Pourqarib, Behzad (Anafora, 2023)
This paper examines the concepts of Wilderness and the Sublime and discusses different views of nature in John Keats’ poetry through the theoretical lens of ecocriticism. Analysing the poems “O Solitude!” (1816), “On the Sea” (1817), “Written Upon the Top of Ben Nevis” (1838), and “La Belle Dame Sans Merci” (1819), it employs two ecocritical approaches – Deep Ecology and “The Dark Mountain Project” – to point out that Keats’ conception of nature is both ecocentric and highly sceptical, apprehensive of humanity’s precariousness and vulnerability in the face of it. It argues that such an oxymoronic, albeit still highly potent and relevant take on the dichotomy between man and nature is in line with Keats’ self-definition as a “chameleon poet” who takes many forms and is able to observe things from different viewpoints.